Understanding Michael Porter : the essential guide to competition and strategy - Magretta, Joan, 1948- (Harvard Business Review Press, 2012)
Examines and explains the revolutionary business frameworks of Michael Porter, with examples to illustrate and update Porter's ideas for achieving and sustaining competitive success.